THROMBOSIS IN CANCER. PART 2 - Yu. A. FEDOTKINA; E. P. PANCHENKO (Атеротромбоз)
Cancer is one of the most significant risk factors for the development of venous thromboembolic complications, and also increases the risk of arterial thrombosis mainly in the coronary and cerebrovascular arteries. The article aimed to examine the direct toxic effects on vascular endothelium demonstrated by specific classes of chemotherapeutic drugs, tumor procoagulant effect, inhibition of endogenous fibrinolysis, and increased platelet aggregation among the pathogenetic mechanisms of these complications. The article is presented in two parts. The first part examines the traits of the hemostasis state in cancer, some pathogenetic mechanisms of arterial and venous thrombosis, and the management of cancer patients with the arterial thrombosis. The second part provides a review of the literature on the prevention and treatment of cancer-associated venous thromboembolic complications.